Understanding Climate Change Through the Eyes of Nepali Urban Children - Dahal, Ishwar Kumar (Literary Studies, 2026)
Research exploring children’s own conceptions and voices regarding climate change in Nepal remains scarce. This study explores how Kathmandu-based children, aged nine to thirteen, understand and emotionally engage with environmental issues through twenty-five in-depth interviews. It further looks into the sources of their information. This paper is guided by Bronfenbrenner’s Ecological Systems Theory and Vygotsky's sociocultural theory to examine how the children’s ecological understanding emerges from interactions within family, peer groups, schools, and media. The findings reveal that children are deeply concerned about environmental degradation, expressing fear, sadness, and anxiety about their future. However, their imaginations are largely shaped by global narratives—rising sea levels, melting ice, and increasing global temperatures—rather than by local ecological challenges. This indicates that Nepali children are active meaning-makers whose environmental awareness is globally mediated yet locally detached. It further suggests that their perceptions are shaped more by media and education than by lived experiences. Understanding how children see these issues is important for creating education programs that connect global climate talks with local environmental problems and help children take an active role in protecting the planet.